Pengaruh Pemberian Edukasi Gizi dan Kapsul Serbuk Daun Kelor (Moringa oleifera L.) terhadap Kenaikan Kadar Hemoglobin Remaja Putri di Universitas Pakuan - Lusi Indriani; Cantika Zaddana; Naufal Muharam Nurdin; Juniarti Sri Maryati Sitinjak (Fakultas Farmasi, Universitas Surabaya, 2019)
Anemia is a condition where the hemoglobin (Hb) level is lower than 12 g/dL. Teenagers are the most susceptible group experiencing a decrease in hemoglobin, especially teenage girls because they get menstruate so that they lose a lot of iron every month. It causes them become easily tired, drowsiness, dizziness, rapid concentration loss, then clearly inhibits the learning process and achievement. Natural ingredients as an alternative to increase Hb which is easily obtained and cultivated are Moringa oleifera L. leaves since they contain protein, vitamin C, and iron. This study aims to evaluate an increase of hemoglobin levels and the knowledge of anemia after giving education and capsules of moringa leaves powder. This is true experimental study with pre and posttest design. The respondents were female students with anemia which were divided to the intervention groups (getting education and kelor) and control groups (getting education and placebo). It was carried out for 30 days. The results showed that education and Moringa leaf powder capsules significantly increased hemoglobin levels by 1.76 ±0.80 g/dL, while the increase in the education group was 0.72 ± 0.97 g/dL. It can be concluded that the education and Moringa leaf powder capsules can significantly increase the knowledge of anemia and Hb levels.